Resilience during the COVID-19 pandemic: Associations with changes in burnout and mental well-being among NHS mental health staff in England - Kika, Natalia; Trompeter, Nora; Lamb, Danielle; Bhundia, Rupa; Carr, Ewan; Dempsey, Brendan; Greenberg, Neil; Madan, Ira; Penfold, Christopher; Raine, Rosalind; Wessely, Simon; Stevelink, Sharon A M (PloS one, 2025)
The pressures of the COVID-19 pandemic placed mental healthcare professionals at an increased risk of burnout and decreased mental wellbeing. Resilience strategies have been put in place as a protective measure, but little is known about how mental wellbeing evolved over time in this group and how resilience affects it. This study aimed to: 1) investigate long-term changes in burnout and mental well-being among mental healthcare professionals working in the National Health Service (NHS) during the COVID-19 pandemic in the United Kingdom (UK); and 2) examine whether baseline resilience levels predicted decreased burnout and increased mental well-being over the course of the pandemic. The study used data from NHS CHECK, a longitudinal cohort study investigating NHS staff mental health and well-being since the COVID-19 pandemic. Clinical mental health staff (n = 3,289) who completed self-report measures at three time points (baseline, 6 and 12 months later). Baseline surveys were conducted during the initial pandemic peak (April 2020 - June 2020; n = 543), the initial easing of restrictions (July 2020 - September 2020; n = 1,098), and the second peak (October 2020 - January 2021, n = 1,648). Mixed model analyses showed that burnout scores increased over time, with higher resilience at baseline predicting lower burnout 6 and 12 months later. However, rises in burnout were most pronounced in the high resilience group. Well-being remained relatively stable over time, with staff with higher resilience at baseline reporting higher well-being over time. Resilience was linked with both lower burnout and higher well-being in NHS mental health staff throughout the COVID-19 pandemic. Despite showing steeper increases in burnout, staff with high initial resilience still maintained lower absolute levels of burnout compared to those with lower resilience. Healthcare organizations should consider providing interventions focusing on organizational factors in addition to individual-level resilience-focused support.